The dubbing effect: an eye-tracking study on how viewers make dubbing work - Romero-Fresco, Pablo (The Journal of Specialised Translation, 2020)
Although dubbing is regularly criticised for its artifice and its manipulation of film sound, it has proved to be the preferred modality of audiovisual translation for millions of viewers. Research in this area has explored at length the way in which the professionals involved in dubbing make it work. What has been overlooked so far is the cognitive process undergone by the viewers to make it work. In order to explore this issue, this paper starts with a discussion of several aspects that may be relevant to the perception and overall reception of dubbing, including cultural arguments on habituation, psychological and cognitive notions of suspension of disbelief and perceptual phenomena such as the McGurk effect. It then goes on to compare, with the help of eye-tracking technology, the eye movements of a group of native Spanish participants watching a clip dubbed into Spanish featuring close-ups with (a) the eye movements of a group of native English participants watching the same clip in English and (b) the eye movements of the Spanish participants watching an original (and comparable) clip in Spanish. This analysis is complemented by data on the participants’ comprehension, sense of presence and self-perception of their eye movements when watching these clips. The findings obtained point to the potential existence of a dubbing effect, an unconscious eye movement strategy performed by dubbing viewers to avoid looking at mouths in dubbing, which prevails over the natural way in which they watch original films and real-life scenes, and which allows them to suspend disbelief and be transported into the fictional world.